2022
DOI: 10.1021/acs.jchemed.2c00105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emotional Intelligence and Demographic Characteristics on Psychological Capital among Chemical Engineering Students

Abstract: Current engineering education should develop the noncognitive abilities of students. Psychological capital (PsyCap) is defined as an individual's strengths of self-efficacy, optimism, hope, and resiliency. PsyCap is an essential noncognitive ability that influences student mental health and academic performance, yet limited research has been done to identify predictors of PsyCap. These predictors might inform the key to developing PsyCap. This study examined the levels of PsyCap and emotional intelligence (EI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
(148 reference statements)
0
5
0
Order By: Relevance
“… Academic Performance (DV): GPA Results indicated that PsyCap was found to mitigate the influence of academic distress on academic performance but not on the influence of academic eustress on academic performance 32 37 Martinez (2019) 8 Spain/Portugal Antecedents of academic performance of university students: academic engagement and psychological capital resources To investigate the relationship between academic engagement, PsyCap, and academic performance In Spain (N ¼ 389) and another in Portugal (N ¼ 243) Academic Engagement (IV): Short (nine-item) Utrecht Work Engagement Scale (Schaufeli, Bakker & Salanova, 2006) PsyCap (MED):12-item (PCQ-12) Academic Performance (DV): GPA Results indicated a positive relationship between academic engagement, PsyCap, and academic performance in both samples. PsyCap is a full mediator in the relationship between academic engagement and academic performance 32 38 Lye (2022) 70 Malaysia Effect of Emotional Intelligence and Demographic Characteristics on Psychological Capital among Chemical Engineering Students To examine the levels of PsyCap and emotional intelligence (EI) and investigated the effects of EI and demographic characteristics on PsyCap 99 final-year chemical engineering students Emotional Intelligence (EI) (IV): The Trait Emotional Intelligence Questionnaire Short Form PsyCap (DV): PCQ Results indicated that specific interventions based on EI are beneficial to developing PsyCap in coping with challenges in their engineering studies and future careers 36 39 Nambudiri (2020) 23 India Student personality and academic achievement: the mediating role of psychological capital (PsyCap) To investigate the role of a second-order state-like construct PsyCap explaining the personality–academic achievement (AA) 305 post-graduate students Student Personality (IV): using the 50-item International Personality Item Pool instrument PsyCap (MED): the 24-item PsyCap questionnaire (PCQ) Academic Achievement (AA) (DV): CGPA Results indicated that PsyCap positively influenced AA. PsyCap mediated the relationship between openness to experience, extraversion, and agreeableness dimensions of student personality and AA 32 40 Geremias (2020) 26 Portugal …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Academic Performance (DV): GPA Results indicated that PsyCap was found to mitigate the influence of academic distress on academic performance but not on the influence of academic eustress on academic performance 32 37 Martinez (2019) 8 Spain/Portugal Antecedents of academic performance of university students: academic engagement and psychological capital resources To investigate the relationship between academic engagement, PsyCap, and academic performance In Spain (N ¼ 389) and another in Portugal (N ¼ 243) Academic Engagement (IV): Short (nine-item) Utrecht Work Engagement Scale (Schaufeli, Bakker & Salanova, 2006) PsyCap (MED):12-item (PCQ-12) Academic Performance (DV): GPA Results indicated a positive relationship between academic engagement, PsyCap, and academic performance in both samples. PsyCap is a full mediator in the relationship between academic engagement and academic performance 32 38 Lye (2022) 70 Malaysia Effect of Emotional Intelligence and Demographic Characteristics on Psychological Capital among Chemical Engineering Students To examine the levels of PsyCap and emotional intelligence (EI) and investigated the effects of EI and demographic characteristics on PsyCap 99 final-year chemical engineering students Emotional Intelligence (EI) (IV): The Trait Emotional Intelligence Questionnaire Short Form PsyCap (DV): PCQ Results indicated that specific interventions based on EI are beneficial to developing PsyCap in coping with challenges in their engineering studies and future careers 36 39 Nambudiri (2020) 23 India Student personality and academic achievement: the mediating role of psychological capital (PsyCap) To investigate the role of a second-order state-like construct PsyCap explaining the personality–academic achievement (AA) 305 post-graduate students Student Personality (IV): using the 50-item International Personality Item Pool instrument PsyCap (MED): the 24-item PsyCap questionnaire (PCQ) Academic Achievement (AA) (DV): CGPA Results indicated that PsyCap positively influenced AA. PsyCap mediated the relationship between openness to experience, extraversion, and agreeableness dimensions of student personality and AA 32 40 Geremias (2020) 26 Portugal …”
Section: Resultsmentioning
confidence: 99%
“…Hicks and Wu 57 found that adaptive perfectionism was associated with higher PsyCap. According to Lye et al, 70 emotional intelligence (EI) is an important factor in predicting PsyCap among engineering students, while age, gender, race, family income, and pre-university education of the students cannot significantly predict PsyCap. Moreover, da Costa et al 55 contented that students’ emotional intelligence is a major factor in PsyCap that goes beyond individual differences and training.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with ordinary students, it is difficult to improve their economic situation through part-time jobs or work-study because of their narrow socialization and insufficient ability to obtain information on work-study. In order not to expose their embarrassment in front of the crowd, they are unwilling to open their hearts to socialize with others [6][7]. When the need to socialize conflicts with their own ability, they are prone to pessimism and disappointment, which further leads to the tendency of psychological closure [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Zhengrong Ding and Yuan Zhou. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] …”
mentioning
confidence: 99%
“…Emotional computing technology represents a burgeoning field at the intersection of psychology, neuroscience, and computer science, aiming to imbue machines with the ability to recognize, interpret, and respond to human emotions [1]. By leveraging advanced algorithms, machine learning techniques, and sensor data, such as facial expressions, voice tone, and physiological signals, emotional computing systems can infer the emotional states of users in realtime [2].…”
Section: Introductionmentioning
confidence: 99%